2009
DOI: 10.1097/won.0b013e3181b35ed1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bodily Pain

Abstract: Compared to patients without venous ulcers, those patients with venous ulcers rated their pain lower and reported higher coping and control over pain, which may be reflected in better subjective pain management despite having more pain sites and disability related to pain. Pain management for indigent patients with and without venous ulcers remains a concern and needs further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 50 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…These two factors lead to changes in the patient’s daily life, well‐being, social and leisure activities, self‐care, and other activities [26, 28, 51, 52]. Pain control in patients with venous leg ulcers is of fundamental importance because it improves quality of life, mobility, sleep quality, and appetite [53, 54]. In our study, patients in the control group reported pain at all four time points, and patients in the surgery group reported improvement in pain 30 days after skin grafting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These two factors lead to changes in the patient’s daily life, well‐being, social and leisure activities, self‐care, and other activities [26, 28, 51, 52]. Pain control in patients with venous leg ulcers is of fundamental importance because it improves quality of life, mobility, sleep quality, and appetite [53, 54]. In our study, patients in the control group reported pain at all four time points, and patients in the surgery group reported improvement in pain 30 days after skin grafting.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted with 40 patients with venous leg ulcers, the prevalence of pain was 90 %, and the mean VAS pain score was 6.2, indicating severe pain [55]. In another study assessing the relationship between pain and functional status, the pain descriptors used by patients with venous leg ulcers were sharp (89 %; sensory class of the MPQ) and nagging (87 %; affective class of the MPQ) [54].…”
Section: Discussionmentioning
confidence: 99%